Examining fear appeals and information seeking in tuberculosis health education campaigns: an experimental test of the extended parallel processing model with perceived barriers as a moderator. - Fu, Lunrui; Han, Huaizhi; Chen, Liang (Health Education Research, 2026)
Tuberculosis (TB) health education campaigns often struggle to motivate at-risk populations by employing one-size-fits-all fear appeals without considering how structural barriers shape audiences' ability to respond. Drawing on the Extended Parallel Processing Model (EPPM), this study tested how varying levels of threat and efficacy in TB messages influence information-seeking intentions, with perceived barriers as a moderator. In a 2 (threat: low versus high) × 2 (efficacy: low versus high) between-subject experiment with 225 Chinese participants, results revealed that high-threat messages increased participants' TB information-seeking intentions compared with low-threat messages. In addition, low-barrier individuals responded best to high-threat, high-efficacy messages; moderate-barrier individuals were motivated by high-threat messages even with low efficacy messages. These findings demonstrate that accounting for structural barriers extends the EPPM framework and provide health educators with a practical framework for audience segmentation and message tailoring.